The use of electronic textbooks at a new stage of educational development (Eurasian Journal of Physics,Chemistry and Mathematics, 2024)
Electronic textbooks have emerged as a pivotal tool in modern education, offering dynamic content delivery, interactive features, and enhanced accessibility. This article explores the role of electronic textbooks in the evolving landscape of education, examining their impact on student learning outcomes, pedagogical approaches, and classroom dynamics. Through a comprehensive literature review, this study evaluates the effectiveness of electronic textbooks, discusses various methodologies for their integration, presents empirical evidence of their benefits, and offers insights into future directions for research and implementation. By embracing electronic textbooks, educators can leverage technology to foster engaging learning experiences, cater to diverse student needs, and propel educational development into a new era.